2019
DOI: 10.36016/jvmbbs-2019-5-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of acute toxicity of the ‘Bondarmin’ disinfectant

Abstract: In the article the results of the study of toxic effect of the designed disinfectant (active ingredient potassium peroxomonosulfate) on laboratory animals (mice) are presented. For the recent years a variety of scientific works both by domestic and by foreign scientists has been devoted to the study of different disinfectants’ toxicity. However today there is a number of issues that require more detailed studying and scientific justification. Among them the problem of toxic effects of disinfectants on the anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…The use of effective and safe disinfectants is of paramount importance in providing the population with quality products of animal origin (Paliy et al, 2017(Paliy et al, , 2018d. One of the main criteria that determines the feasibility of using disinfectants in practical conditions is their environmental safety and low toxicity to staff and animals (Du et al, 2017;Bondarchuk et al, 2019). In the development of intoxication of the macroorganism with potent toxic substances there are four periods: the period of contact; hidden period; period of toxic pulmonary edema; period of complications (Presgrave et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The use of effective and safe disinfectants is of paramount importance in providing the population with quality products of animal origin (Paliy et al, 2017(Paliy et al, , 2018d. One of the main criteria that determines the feasibility of using disinfectants in practical conditions is their environmental safety and low toxicity to staff and animals (Du et al, 2017;Bondarchuk et al, 2019). In the development of intoxication of the macroorganism with potent toxic substances there are four periods: the period of contact; hidden period; period of toxic pulmonary edema; period of complications (Presgrave et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The problem of parasitic diseases of agricultural and domestic animals remains relevant today (Paliy et al, 2018a;2018b;2018c;, despite the introduction of new high-performance anthelminths (Lloyd et al, 2000;Lambertz et al, 2019;Preston et al, 2019) and disinfectants (Paliy et al, 2015;2020a;Stegniy et al, 2019;Bondarchuk et al, 2019). Most recently, the results of advanced studies of ostrich parasites (Struthio camelus), mainly from European countries where commercial ostrich farming is gaining momentum (Cooper, 2005) have been published.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that the dosage form and manufacturing technology of drugs are also essential and their physical state, the properties of the constituent components, and the route of administration into the body (Pink et al, 2005;Mukherjee et al, 2016). The study of their toxic effects on biological objects is an intermediate stage in testing new chemical compounds (Bondarchuk et al, 2019;Orobchenko et al, 2020;Kovalenko et al, 2020). The research aim was to estimate the suggested innovative complex veterinary drugs.…”
Section: Effectiveness Of a Modern Antiparasitic Agentmentioning
confidence: 99%